Pengaruh Aglomerasi Industri dan Tingkat Pengangguran Terbuka terhadap Ketimpangan Wilayah dalam Perspektif Ekonomi Islam: Analisis Data Panel Periode 2018–2024 di Wilayah Jabodetabek - Satrio Budi Wijaya; Heni Noviarita; Weny Rosilawati (Indonesian Journal of Islamic Economics and Business, 2026)
This study aims to analyze the impact of industrial agglomeration and the open unemployment rate on regional economic inequality in the Greater Jakarta area (Jabodetabek) for the period 2018–2024 from an Islamic economic perspective. Regional inequality is a significant issue that reflects the uneven distribution of income and economic activity across regions. This study employs a quantitative method using a panel data regression approach, selecting the Common Effects Model (CEM), Fixed Effects Model (FEM), and Random Effects Model (REM). The results indicate that the best model is the Fixed Effect Model (FEM), where industrial agglomeration and the open unemployment rate have a partial, negative, and significant effect on regional inequality. These findings suggest that the dynamics of economic distribution across regions influence the level of inequality.From an Islamic economic perspective, these results reflect the importance of applying the principles of justice (al-‘adl) and balance (tawazun) in economic development to reduce disparities regions.